2004
DOI: 10.1021/jo035058l
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Spiro- and Fused-Ring Heterocycles via Oxidative Demetalation of Cyclohexadienyl Ruthenium Complexes

Abstract: Electron-rich alkoxy- and chloro-substituted azaspirocyclic cyclohexadienyl Ru(II) complexes have been converted to either azaspiro[4.5]decane derivatives or functionalized tetrahydroisoquinolines by treatment with suitable oxidizing agents. Copper(II) chloride was found to provide demetalated products in high yield relative to the other oxidants examined (FeCl(3), DDQ, CAN, [Cp(2)Fe][PF(6)], phenyliodine diacetate, IBX). In certain instances, the efficiency of oxidative demetalation was enhanced by the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The 1 H NMR signal for the benzyl protons of 4b can be observed at δ ϭ 3.67 ppm in acetonitrile (or CD 3 OH) but disappears within 5 min in D 2 O or CD 3 OD. The responsible rapid H/D exchange in the latter solvents is clearly a consequence of the relatively high acidity of the methylene protons in 4b as a result of both the η 6 -coordination of the phenyl group [25,26] and the presence of a neighbouring carboxylate group. A similar H/D exchange is also observed for 4a in CD 3 OD but not for the η 6 -phenylbutyric acid complex 5 with its longer side-chain.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR signal for the benzyl protons of 4b can be observed at δ ϭ 3.67 ppm in acetonitrile (or CD 3 OH) but disappears within 5 min in D 2 O or CD 3 OD. The responsible rapid H/D exchange in the latter solvents is clearly a consequence of the relatively high acidity of the methylene protons in 4b as a result of both the η 6 -coordination of the phenyl group [25,26] and the presence of a neighbouring carboxylate group. A similar H/D exchange is also observed for 4a in CD 3 OD but not for the η 6 -phenylbutyric acid complex 5 with its longer side-chain.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Pearson's work dominates the field of the synthesis of naturally occurring diaryl ethers by this method (Scheme 2, R 1 = η 6 -Ru + CpPF 6 -). [15] Pearson's work dominates the field of the synthesis of naturally occurring diaryl ethers by this method (Scheme 2, R 1 = η 6 -Ru + CpPF 6 -).…”
Section: S N Ar Additions To Metal-arene Complexesmentioning
confidence: 99%
“…(D) Pigge and coworkers reported that the ruthenium complex when exposed to 3 equiv of PDC, SiO 2 , CH 2 Cl 2 , r.t., 5 gives metalfree dienones 1 and 2 (1:2 ratio, respectively), albeit in somewhat modest 48% overall yield. 6 (E) Brown et al showed that a primary-carbon-boron bond can be cleaved and oxidized to carboxylic acid by using PDC in DMF. 7 (F) Schepens et al described that after protection of the carbonyl group as ethylene ketal (96% yield) the allylic position can be oxidized to an enone with PDC and tert-butylhydroperoxide in 64% yield.…”
Section: Abstractsmentioning
confidence: 99%
“…Pyridinium dichromate (PDC) is a mild and selective oxidizing agent mainly used to oxidize primary 1 and secondary alcohols. 2 It has several other applications such as in the rearrangement of allylic hydroxyl groups, 3 in the preparation of heterocycles, 4 the production of metal-free dienones, 5,6 the oxidation of carbon-boron bonds 7 as well as in the preparation of enones 8 and in multicomponent reactions. 9 This reagent was discovered by E. J. Corey and G. Schmidt in 1979.…”
Section: Introductionmentioning
confidence: 99%